YCHSMA TEXTILES OF LATE HORIZON IN THE BURIAL OF ARMATAMBO - Frame, Mary (2012)
A burial context, excavated in 1982 at Armatambo, provides the basis for describing the Ychsma textile style during the Late Horizon. The textile data (types of garments, images, design lay-out, fibers, fabric structures, yarn spin, colors, etc.) are extensive enough to distinguish many types of Ychsma-style garments from those of other styles, and to identify similar textiles in museum collections. The provenience information on Ychsma textiles from museum collections suggests the extent of the Ychsma sphere of interaction on the Central Coast.